Laboratory Diagnosis of Helicobacter pylori Infection: Current Methods and Clinical Applications - Alamer, Mohammed Ali; Bajawi, Yahya Mohammad; Al-Mojali, Mohammed Abdulrahman; Alturaqi, Maram Abdullah; Alenazi, Yasmeen Mohammed; Alreesh, Amani Emad Abu (Journal of Posthumanism, 2026)
Helicobacter pylori (H. pylori) infection affects approximately half of the global population and represents a significant risk factor for peptic ulcer disease, gastric adenocarcinoma, and mucosa-associated lymphoid tissue lymphoma. Accurate laboratory diagnosis is essential for appropriate treatment and disease prevention. This review examines current laboratory diagnostic methods for H. pylori infection, including invasive and non-invasive approaches. Invasive methods requiring endoscopy include rapid urease test, histopathology, culture, and molecular testing. Non-invasive methods include urea breath test, stool antigen test, and serological antibody detection. Each method has distinct advantages, limitations, and clinical applications. The selection of appropriate diagnostic testing depends on clinical presentation, previous treatment history, local antibiotic resistance patterns, and test availability. Understanding the performance characteristics and appropriate use of laboratory tests is crucial for optimal patient management.